Early identification of low employability graduate in Malaysia : the use of proportional hazard model / Lim Hock-Eam - Lim, Hock-Eam (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2005)
This paper illustrates the use of statistical prediction model for early identification of low employability Malaysian graduates using the proportional hazard model. The relative predicted hazard rate or probability of exit from unemployment is used to proxy the graduate's employability. The out-of-sample evaluation shows that the statistical prediction model predicts correctly 83%, 75% and 80% of the graduates that identified at bottom 15%, 20% and 25% of employability respectively. The estimated probability of exit from unemployment also suggests that nine months is the reasonable expected unemployment duration for Malaysian graduates.